FABRICATION AND SCREENING OF SOLID LIPID NANOPARTICLES-LOADED MICRONEEDLE PATCH FOR POLYCYSTIC OVARY SYNDROME TREATMENT - FORAM BHATT; DIPTI PATEL (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The study aimed to develop a novel microneedle (MN) patch for the transdermal delivery of clomiphene citrate. This approach seeks to facilitate sustained drug release through the skin, improving therapeutic efficacy and minimizing side effects associated with oral administration. Methods: The patch was constructed using biocompatible polymers – polyvinyl alcohol, polyvinylpyrrolidone, and polyethylene glycol 400 – commonly utilized in medical applications. Each MN measured approximately 915 μm in height, optimized to penetrate the outer skin layer without causing pain. Durability was assessed by folding the patch repeatedly; it withstood nearly 300 folds before exhibiting signs of wear. Analytical tests confirmed that clomiphene citrate remained stable within the patch matrix, with no adverse interactions between the drug and the polymer components. In vitro experiments using simulated human skin models demonstrated a biphasic release pattern: an initial rapid release followed by a sustained release over 5 days. Human skin samples were employed to evaluate the patch’s drug release profile, corroborating the in vitro findings. The patch’s efficacy was tested on rats with letrozole-induced fertility issues, simulating human infertility conditions. Results: Microscopic examination revealed uniformly shaped MNs of appropriate dimensions for effective skin penetration without discomfort. The patch demonstrated high durability, maintaining structural integrity after extensive mechanical stress. The drug and polymer components exhibited compatibility, ensuring the stability of clomiphene citrate within the patch. Approximately 89% of the drug was released over 5 days in vitro, while ex vivo tests showed a 78% release, indicating effective sustained delivery. In vivo studies indicated that the transdermal delivery of clomiphene citrate through the MN patch (MNP) resulted in prolonged drug activity and reduced side effects compared to oral administration. Conclusion: The MNP developed in this study offers a promising alternative for the transdermal delivery of clomiphene citrate. Its design ensures painless application, sustained drug release, and improved therapeutic outcomes, potentially reducing the side effects associated with traditional oral administration.